Studies on Glucose Lowering Efficacy of the Anthocephalus Cadamba (Roxb.) Miq. Roots. - S. ACHARYYA; G. K. DASH; S. MONDAL; S.K. DASH (International Journal of Pharma and Bio Sciences, 2010)
Diabetes, the most prevailing metabolic disorder is attracting present research attention towards it. The methanol and aqueous extracts of the roots of Anthocephalus cadamba (Roxb.) Miq. (Family-Rubiaceae) was tested for hypoglycaemic activity in normoglycaemic and alloxan induced hyperglycaemic rats at dose levels of 100, 200 and 400 mg/kg, p.o. respectively. The extract was further subjected to oral glucose tolerance test in normal rats. The hypoglycaemic activity of the root was compared with the reference standard glibenclamide (2.5 mg/kg, p.o.). The study revealed that the roots extract caused significant reduction in the blood glucose level in both normoglycaemic and alloxan induced diabetic rats at the tested dose levels in a dose dependant manner. In glucose-loaded animals, the extract also reduced the elevated blood glucose concentration. The study established the scientific basis for the utility of this plant in the treatment of diabetes and justifies the use of the roots of the plant for treating diabetes as suggested in folklore remedies.